EFFECTIVENESS OF BREAST CRAWL BY MIDWIVES TO INCREASE BREAST MILK PRODUCTION AMONG POSTPARTUM MOTHERS - Sultina Sarita; Syahrianti Syahrianti; Nurnasari P (Public Health of Indonesia)
Background: Normal Childbirth Care or APN is a standard or a reference for childbirth assistance and a breast crawl, or called IMD, in Indonesia; however, there is lack of its implementation in the midwifery practice. Breast crawl is considered effective in increasing breast milk production among postpartum mothers.